2014
DOI: 10.1155/2014/306325
|View full text |Cite
|
Sign up to set email alerts
|

Functional Brain Correlates of Upper Limb Spasticity and Its Mitigation following Rehabilitation in Chronic Stroke Survivors

Abstract: Background. Arm spasticity is a challenge in the care of chronic stroke survivors with motor deficits. In order to advance spasticity treatments, a better understanding of the mechanism of spasticity-related neuroplasticity is needed. Objective. To investigate brain function correlates of spasticity in chronic stroke and to identify specific regional functional brain changes related to rehabilitation-induced mitigation of spasticity. Methods. 23 stroke survivors (>6 months) were treated with an arm motor learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
(40 reference statements)
3
10
0
Order By: Relevance
“…Alleviation of PSS at W4 was associated with an apparent reduction in the extent of activation, mostly of the bilateral parietal cortices and cerebellum, but returned close to the original extent at W11. This finding is in agreement with our previous studies and other previously published fMRI studies uncovering cerebral correlations with PSS treatment (1416, 20, 4952). Extended task-related cortical activation probably represents a general response of the lesioned brain to increased proprioceptive afferent input associated with PSS (13, 14).…”
Section: Discussionsupporting
confidence: 94%
“…Alleviation of PSS at W4 was associated with an apparent reduction in the extent of activation, mostly of the bilateral parietal cortices and cerebellum, but returned close to the original extent at W11. This finding is in agreement with our previous studies and other previously published fMRI studies uncovering cerebral correlations with PSS treatment (1416, 20, 4952). Extended task-related cortical activation probably represents a general response of the lesioned brain to increased proprioceptive afferent input associated with PSS (13, 14).…”
Section: Discussionsupporting
confidence: 94%
“…This study revealed a significant reduction in spasticity following rPMS along with a stronger mu rhythm ERD in the contralesional hemisphere. This is consistent with the results of Pundik et al ( 39 ) and Miyara et al ( 40 ). Pundik et al identified a positive correlation between decrease in spasticity and the strength of fMRI activation in the contralesional motor cortex.…”
Section: Discussionsupporting
confidence: 94%
“…By contrast, the present study adopted EEG to measure cortical activity. Stronger activations in the contralesional hemisphere have been detected using fMRI ( 39 ) and fNIRS ( 40 ); this is in agreement with the EEG results of the present study, which revealed decreased ERD power in the contralesional hemisphere. This finding may indicate that activity changes in the contralesional hemisphere are associated with decreases in spasticity.…”
Section: Discussionsupporting
confidence: 92%
“…A recent publication used another standardized clinical measure of spasticity, the Modified Ashworth Scale (MAS), and evaluated summed scores across upper extremity muscle groups to reflect a primary outcome measure (Pundik et al, 2014). Based on this precedent, and the expectation that we might see improvement in multiple muscles along the path of current flow, we utilized summed scores for the MTS across the upper extremity muscles (MTS UE ), as the MTS has been demonstrated to be more sensitive to changes in spasticity as compared to the MAS (Haugh et al, 2006;Akpinar et al, 2017;Mehrholz et al, 2005).…”
Section: Clinical Assessments Modified Tardieu Scale (Mts)mentioning
confidence: 99%